Taunay e a legitimidade literária: um apelo ao leitor do futuro - Paula, Luciano Melo de (2017)
This work is dedicated to the research, presentation and evaluation of the work of Alfredo d'Escragnolle Taunay (1843 - 1899), the Viscount of Taunay. Our approach focuses on the identification and contextualization of Taunay's efforts to affirm his literary legitimacy. In this sense, we will highlight the initial period of publication of the works of this author, between 1867 and 1874; as well as the reflections present in Memórias (TAUNAY, 1948a), posthumous text, in which he appeals to his readers of the future for a positive reconsideration of his production and his military and political careers. The first works of Taunay - with emphasis on Inocência (TAUNAY, 1872) and Histórias Brasileiras (TAUNAY, 1874) - contributed to the renewal and updating of the themes, scenarios and types proper to the literature produced in Brazil at the end of the century XIX, and also, at least in the first half of the twentieth century. The emphasis on the early Taunay works will be complemented by the description of his appeal to readers of the future for a valuation of his work distinct from that presented by his contemporaries. This appeal and claim to the future will be the most reiterated questions in Memórias (TAUNAY, 1948a). For this, we will describe the circumstances of production and publication of this book, we will comment on its content and the sources of the style employed, as well as the planned strategy of publication of this material. Taunay, in his memorialistic writings, retrieves and preserves for posterity the direct testimony of those who witnessed events and decisive processes of that Brazilian historical period. It does more than just record, comment and offer information in the first person so that such events and processes can be known and evaluated in their multiple meanings. The war in Paraguay, the campaign for the abolition of slavery, European immigration and the republican movement are some of the in-depth themes that Taunay helps to clarify with his memorialistic texts.